Cyberbullying Among Minors and Early Prevention Measures - Hernawati RAS; Jhon Asron Purba; Rusdi Rusdi; Roni Eka Putra (International Journal Labs, 2026)
This study aims to analyze the phenomenon of cyberbullying among adolescents and the early prevention measures that can be applied. Cyberbullying is a form of online violence carried out through social media and other digital platforms that can cause serious psychological impacts on victims, including anxiety, depression, and even suicide. Using a qualitative method based on a case study approach, this research analyzes the characteristics of cyberbullying behavior, its underlying causes, and the negative impacts it has on adolescents. Data were collected through library research, observations, and interviews with experts and education practitioners. The findings show that cyberbullying is often triggered by personal characteristics, perceptions of the victim, and a lack of empathy among perpetrators. Furthermore, the roles of parents, schools, and society are crucial in the prevention and management of cyberbullying. This study suggests the importance of early digital literacy education, stricter parental supervision of children's social media use, and the role of schools in establishing rules and policies that support cyberbullying prevention. In conclusion, addressing cyberbullying requires a comprehensive approach from all relevant parties to create a safe environment for adolescents in the digital world.